A Sudanese Scholar in the Diaspora: Life and Career of Ahmad Muhammad al-Suritti in Indonesia - Abushouk, A. Ibrahim (Studia Islamika, 2001)
This article will examine early life and career of Ahmad Muhammad al-Surkitti in the Sudan and Saudi Arabia, and critically assess his contribution to the Islah and Tajdid movements in Southeast Asia. Special attention will be as well paid to his intellectual and religious encounter with the 'Alawi Sayyids, who branded him as a "Wahhabi" and sometimes as a "preacher of the Sudanese Mahdi's teachings" in the Netherlands East Indies.DOI: 10.15408/sdi.v8i1.695